2015
DOI: 10.1007/s10964-015-0389-7
|View full text |Cite
|
Sign up to set email alerts
|

Sports Participation and Juvenile Delinquency: A Meta-Analytic Review

Abstract: Participation in sports activities is very popular among adolescents, and is frequently encouraged among youth. Many psychosocial health benefits in youth are attributed to sports participation, but to what extent this positive influence holds for juvenile delinquency is still not clear on both the theoretical and empirical level. There is much controversy on whether sports participation should be perceived as a protective or a risk factor for the development of juvenile delinquency. A multilevel meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 97 publications
(126 reference statements)
0
38
0
9
Order By: Relevance
“…Systematic review studies have summarized evidence on participation in sports and selected health‐related behaviors, such as drug and alcohol use, juvenile delinquency, and psychological and social benefits . Few studies to date have, however, reported on various healthy and unhealthy lifestyle behaviors among a large sample of adolescents in relation to OSP .…”
Section: Introductionmentioning
confidence: 99%
“…Systematic review studies have summarized evidence on participation in sports and selected health‐related behaviors, such as drug and alcohol use, juvenile delinquency, and psychological and social benefits . Few studies to date have, however, reported on various healthy and unhealthy lifestyle behaviors among a large sample of adolescents in relation to OSP .…”
Section: Introductionmentioning
confidence: 99%
“…Part‐time employment can be a risk factor for joining gangs, and for an increase in alcohol and marijuana use in adolescents due to a connection with sensation‐seeking and impulsivity . A recent meta‐analysis also indicated that sports participation is not associated with juvenile delinquency . Another study observed a negative influence of social integration into a social environment favoring substance use: being integrated into networks is associated with higher likelihood of cigarette smoking among adolescents .…”
Section: Discussionmentioning
confidence: 99%
“…29 A recent meta-analysis also indicated that sports participation is not associated with juvenile delinquency. 30 Another study observed a negative influence of social integration into a social environment favoring substance use: being integrated into networks is associated with higher likelihood of cigarette smoking among adolescents. 31 It is possible that when adolescents participate in highly structured activities that require a higher level of skill building, such as sports, music or art clubs, they are less likely to be associated with problem behavior than those who participate in low-structure activities.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of youth sport has garnered significant interest across disciplines, with studies examining the potential health impacts of sport participation [ 20 , 21 ], academic impacts [ 22 , 23 ], social and psychological impacts on the youth [ 7 ], impacts on delinquency [ 10 ], and societal benefits [ 24 , 25 ]. Measuring youths’ experience in sport is essential to advance research across disciplines.…”
Section: Introductionmentioning
confidence: 99%